2011
DOI: 10.1029/2011gl048783
|View full text |Cite
|
Sign up to set email alerts
|

Mapping near-inertial variability in the SE Bay of Biscay from HF radar data and two offshore moored buoys

Abstract: .[1] HF radar surface current data together with data from two operational offshore oceanographic buoys located over the slope are used to map the variability associated with the near-inertial waves, during a target year (2009), in the SE Bay of Biscay. The results obtained show the complex 4D distribution of inertial oscillations in this area. We find a very pronounced horizontal structure across the area with ranges of a factor 5 in near-inertial kinetic energy. This pattern presents also strong seasonal var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
50
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 21 publications
11
50
0
Order By: Relevance
“…In addition, parameters related to errors due to the geometrical dilution of the precision are calculated and controlled when deriving total velocities from radials. Eulerian comparison between the HF radar data and other available in-situ data in the SE Bay of Biscay has been performed in previous work [14,15,16]. The comparison between radar data and the currents at 1.…”
Section: A Hf Radar Datamentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, parameters related to errors due to the geometrical dilution of the precision are calculated and controlled when deriving total velocities from radials. Eulerian comparison between the HF radar data and other available in-situ data in the SE Bay of Biscay has been performed in previous work [14,15,16]. The comparison between radar data and the currents at 1.…”
Section: A Hf Radar Datamentioning
confidence: 99%
“…At shorter time-scales, the variability is dominated by inertial oscillations and tides (mainly semidiurnal), although energy contents around the main tidal peaks are lower than in other areas of the Bay [13]. Reference [14] discussed on the contribution of inertial oscillations to the shear-induced vertical mixing in this area [3] and, from HF radar data in 2009, showed that the distribution of kinetic energy around the inertial band was highly variable in time and space [14].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A growing number of European studies have been developed on the use of HFR data toward a better understanding of the surface ocean coastal dynamics (Shrira et al, 2001;Rubio et al, 2011;Schaeffer et al, 2011;Uttieri et al, 2011;Sentchev et al, 2013;Berta et al, 2014a;Shrira and Forget, 2015;Stanev et al, 2015;Falco et al, 2016). Moreover, since HFR data provide measurements of currents with a relatively wide spatial coverage and high spatial and temporal resolution in near real time (there are systems with lags of just 20 min, after generating the data), they have become invaluable tools in the field of operational oceanography.…”
Section: Introductionmentioning
confidence: 99%
“…Standard quality control procedures were applied to radial and total velocities (Rubio et al, 2011). The HF radar currents were validated by Rubio et al (2011); these authors concluded that the HF radar currents agree well with in situ measurements in the area.The wind components at 10 m a.s.l. of the Climate Forecast System Reanalysis (CFSR), provided by the National Centers for Environmental Prediction (NCEP), were also analysed in this study (Saha et al, 2010).…”
Section: Methodsmentioning
confidence: 99%